Child with cerebrospinal fluid rhinorhoea complicated by recurrent meningitis - Sumanasena, S. P.; Lamabadusuriya, S. P. (Sri Lanka College of Paediatricians, 2005)
Recurrent meningitis in children may be due to immune deficiency, presence of indwelling devices in the ventricular system or breakage of the mucocutaneous barrier between skin and cerebrospinal fluid (CSF). We report a child who presented with recurrent meningitis and CSF rhinorrhoea due to presence of a defect in the cribriform plate.

Introduction Recurrent meningitis in children may be due to immune deficiency, presence of indwelling devices in the ventricular system or breakage of the mucocutaneous barrier between skin and cerebrospinal fluid (CSF). We report a child who presented with recurrent meningitis and CSF rhinorrhoea due to presence of a defect in the cribriform plate
Keywords: cerebrospinal rhinorrhoea; recurrent meningitis; child